Portfolio assesment in ESL writing classrooms / Teti Rozi Ariffin - Ariffin, Teti Rozi (2008)
This qualitative case study examines portfolio assessment as an alternative tool in ESL writing classrooms of a class of students with limited language proficiency. Airasian (2002) has highlighted that portfolio assessment is a collection of selected students’ work to demonstrate their work and accomplishment over time to show their growth and development. This school is situated in a suburban area of Kuala Terengganu. The purpose of this study was to examine the effects of using portfolio assessment in ESL classrooms particularly towards writing essay, the students’ and teachers’ perceptions of having this portfolio assessment, the issues and challenges of portfolio assessment in ESL classrooms. The investigation employed qualitative research techniques. Data were collected from students’ portfolio which consisted of essays and learning journal, interviews with the students and teachers, and questionnaire for both groups. Thirty-three students were involved in the study and all submitted their complete portfolios. Data analysis revealed that most students preferred using portfolio assessment and admitted to getting better in writing English. Students reflected on learning their strengths and weaknesses through portfolio assessment. Teachers liked portfolio assessment but worried that the students’ proficiency level could not make it effective and successful. Few suggestions were recommended in making portfolio assessment a successful alternative assessment to the standardized testing.